2004
DOI: 10.1159/000076839
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodestructive Procedures

Abstract: Methods used in laser destructive procedures are detailed. While in noncontact procedures laser energy is delivered via the optics of a slitlamp, often enhanced by contact lenses, the contact method takes advantage of optical fibers for the delivery of energy. Endpieces such as hemispherical or microlens probes enhance the cyclodestructive effect and/or allow the dose of laser energy to be reduced. Laser energy may also be delivered under direct view by endoscopic systems. Advances in laser cyclodestruction ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although both TSCPC and CCT techniques have proven effective, there have been concerns regarding postoperative complications, particularly with the latter. The most commonly reported complications include postoperative pain, anterior chamber reaction, corneal oedema, and hyphema (Dastiridou et al, 2018; Fankhauser & Kwasniewska, 2004; Ndulue et al, 2018). Previous research suggested that CCT resulted in more postoperative pain, vision loss, and devastating sequelae (Benson & Nelson, 1990; Goldenberg‐Cohen et al, 2005; Krupin et al, 1978; Wagle et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although both TSCPC and CCT techniques have proven effective, there have been concerns regarding postoperative complications, particularly with the latter. The most commonly reported complications include postoperative pain, anterior chamber reaction, corneal oedema, and hyphema (Dastiridou et al, 2018; Fankhauser & Kwasniewska, 2004; Ndulue et al, 2018). Previous research suggested that CCT resulted in more postoperative pain, vision loss, and devastating sequelae (Benson & Nelson, 1990; Goldenberg‐Cohen et al, 2005; Krupin et al, 1978; Wagle et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…CW-TSCPC is performed using the Cyclo G6® Laser System and the G-Probe® Delivery Device (IRIDEX Corp., Mountain View, CA). CW-TSCPC is an established cycloablative treatment that achieves IOP reduction through the destruction of the ciliary body to suppress aqueous humor production [ 22 – 26 ] using 810 nm laser energy [ 27 , 28 ]. The footplate of the G-Probe is held parallel to the visual axis with the shorter edge of the footplate firmly between the anterior border and the middle of the limbus which places the laser fiberoptic over the pars plicata.…”
Section: Introductionmentioning
confidence: 99%